Alumni revival: connecting the past, leading the future / Nur Anisya Morshidi ... [et al.] - Morshidi, Nur Anisya; Syed Akil, Sharifah Nur Amirah; Guyang, Martina Emelda; Umbat, Anjeli (Perpustakaan Tun Abdul Razak, UiTM Sarawak, 2023)
Alumni Revival means the process of reconnecting with and engaging former students or graduates of an educational institution, such as a university or college, who have lost touch with the school or their fellow alumni, is referred to as alumni revival. It include attempts to rekindle alumni connections, devotion, and commitment, eventually establishing a stronger alumni community.